Profile of Biology Teachers' Skills in Senior High School in Designing Design Thinking-Based Teaching Materials to Improve Students' Critical Thinking, Numeracy, and Creative Thinking Abilities - Khoerunnisa, Rani Siti; Eni Nuraeni; Anugrah Ayumaharani; Fitri Husni Mardiyah; Dita Astriningrum; Susanti, Dewi (Journal of Biology Education, 2025)
This study aims to describe the profile of senior high school biology teachers’ skills in designing teaching materials based on Design Thinking to enhance students’ critical thinking, numeracy, and creative thinking skills. A descriptive method was employed using an assessment rubric for product of module and rubric of Design Thinking-based modules covering seven aspects. Data were collected through the evaluation of teaching materials designed by biology teachers, focusing on organic waste management. The results indicate that the overall quality of the modules was categorized as “very good,” with an average validator score of 3.55. Teachers’ skills in applying the Design Thinking stages were also categorized as “very good,” with an average score of 3.68 out of 4.00. The highest scores were obtained in the empathize and define stages (4.00), while the lowest score was found in the test stage (3.29). The integration of 21st-century skills was considered good, with a score of 3.33 for formulating learning objectives and 3.48 for developing critical thinking, numeracy, and creative thinking skills. Overall, teachers demonstrated good competence in designing Design Thinking-based modules, although improvements are needed in prototype testing and the consistent integration of 21st-century skills. This study recommends further training and mentoring to enhance the quality of innovative teaching materials that align with the demands of 21st-century education